A self-powered 2D barcode recognition system based on sliding mode triboelectric nanogenerator for personal identification. (January 2018) - Chen, Jie; Pu, Xianjie; Guo, Hengyu; Tang, Qian; Feng, Li; Wang, Xue; Hu, Chenguo
Abstract: Triboelectric nanogenerator (TENG) for developing self-powered personal identification system exhibits great advantages, however, some problems (swiping speed, stability, etc.) in the previous research work prevent this kind of barcode system for further applications. Herein, in this paper, we design a triboelectric based barcode recognition system (T-BS) for practical applications. By using a reference barcode component, the output signal under random swiping motion can be easily recognized, which offers an excellent strategy for the solution of the problems in the previous work. Through the conjunction of threshold value, phase difference and peak-searching, the output voltage signals of the device can be converted into digital signal "1" or "0", and the coded information can be real-time displayed on LabVIEW platform. When swiping a card at a constant speed, or non-uniform speed by human hands, the coded information can be successfully identified and the access control system operates accurately. Moreover, by increasing the numbers of barcode columns and minifying the size, more precise 2D barcode recognition system (including barcode and reader) is obtained and realized the personal identification. This work demonstrates the possibility of the sliding mode TENG as a self-powered 2D barcode recognition system for personal identification, which indicates potential applications in information security. Graphical abstract: Highlights: Using sliding mode TENG, we proposed a self-powered 2D barcode recognition system. Introducing reference barcode, the unstable identification at random sliding speed was solved. Self-powered access control system has been successfully demonstrated. Personal identification system was developed using 2D triboelectric barcode.